Socio-demographic mobility of Maguindanaon migrants in Davao City an exploratory study - Makalasay, Zenaida U.
The setting of the study is the Muslim village in Times Beach, Davao City. It is one of the two identified "known" territories of the Maguindanaon in the City. Muslim comunities in Davao City have always been characterized by its distinct ethnic composition. Despite migration, various Muslim ethnolinguistic groups tend to form their own community and thus create a certain territoriality. The socio-demographic profile and mobility of the Maguindanaon has been slowly changing over time. The aim of the study is to describe and explore the dynamics of the socio-demographic mobility of the Maguindanaon migrants i the City and the factors that can be attributed these changes. To obtain the necessary data, an interview schedule was conducted among fifty (50) Maguindanao household heads which were chosen through simple random sampling. In general, migration affects their spatial distribution as they have been known to be traditionally concentrated in rural areas like Cotabato and Maguindanao. Their household structure tends to be nuclear and family size smaller. The comparison of the Maguinadanaon and their parents' educational attainment shows a certain level of intergenerational mobility already. Maguindanaon woen, despite their educational attainment, have lower if not lesser opportunity for occupational mobility as most of them are confined in housekeeping. In general occupational mobility of the Maguindanaon is viewed in this study in two perspectives: a) in comparison with their fathers'occupation and b) occupation before and after migration. From largely agricultural-based occupations of their fathers, more Maguindanaon are already entering the informal and service sector. The occupation of the respondents before and after migration shows no significant difference at all as most of the occupations they held are menial and low-productive in nature. Establishment of Muslim communities like that of the Muslim Village in Times Beach is inevitable as Maguindanaon migrate from their place of origin because of the social and economic condition such as the peace and order problem that they frequently encounter and the poverty that they are experiencing. Hence, it is not suprising that majority of the Maguindanaon respondents no longer express any desire to go back to their place of origin and thus prefer to live here in the city.